Global, regional, national epidemiology and trends of Parkinson’s disease from 1990 to 2021: findings from the Global Burden of Disease Study 2021 - Luo, Yuanrong; Qiao, Lichun; Li, Miaoqian; Wen, Xinyue; Zhang, Wenbin; Li, Xianwen (Frontiers in Aging Neuroscience, 2025)
AimsIn light of the escalating global incidence of Parkinson’s disease and the dearth of therapeutic interventions that can alter the disease’s course, there exists an urgent necessity to comprehensively elucidate and quantify the disease’s global burden.MethodsThis study analyzed the incidence, prevalence, and disability-adjusted life years (DALYs) of Parkinson’s disease at global, regional, and national levels based on the Global Burden of Disease Study 2021. Bayesian age-period cohort (BAPC) analysis was used to predict the burden in Parkinson’s disease from 2022 to 2035.ResultsIn 2021, 11.77 million people worldwide had Parkinson’s disease. Age-standardized rates of incidence, prevalence, and DALYs increased to 15.63/100,000, 138.63/100,000, and 89.59/100,000. The burden of Parkinson’s disease were higher in males than in females, and showed an increase and then a slight decrease with age. The disease burden was highest in East Asia. BAPC projection showed an increase in all metrics by 2035 except for a slight decrease in the age-standardized DALYs rates.ConclusionThe global burden of Parkinson’s disease has risen over the past 32 years, and there is a need to focus on key populations, as well as to improve health policies to prevent and treat Parkinson’s disease.